Reliability and Validity of Recreational Fishing Motivation Scale inTurkish Population - Faik Ardahan (Selcuk University, 2014)
The purpose of this study was to identify reliability and validity of The Recreational Fishing Motivation Scale in Turkish population. The sample of current study was consisted of 359 volunteer participants (Mage=35.90 ± 9.80) who live in all around of Turkey. In the statistical analysis, scale exploratory factor analysis was conducted to identify the sub-factors of the 21 items which were grouped under six sub-factors. These factors are; socialization, rest and being in nature, competition and glory, escape, eat, and give. Whether the data was suitable to this analysis, Kaiser Mayer Olkin (0.807) and Bartlett Spheritiy test (p lt;0.05) results were taken into consideration. Cronbach's Alpha internal consistency test (0.843) was applied to the identified sub-factors and overall scale. The variance explained by these subscales was %64.590. Finally, results revealed that Recreational Fishing Motivation Scale was a reliable and valid scale in the estimation of the motivational factors for recreational fishing in Turkish population.